Implementasi Sistem E-Commerce Berbasis Web dengan RajaOngkir dan Midtrans untuk Penjualan Batu Akik di Desa Tunjungmuli - Andi Badrun; Anisa Lutfiyani (Politeknik Piksi Ganesha Indonesia, 2026)
The advancement of internet technology has transformed global business through e-commerce. For agate gemstone craft MSMEs in Tunjungmuli Village, whose products possess high economic value due to their aesthetic appeal and rarity, adopting an information system is a strategic way to expand market reach. However, reliance on conventional marketing methods has limited sales growth and market accessibility. This Research and Development (R&D) study employed the ADDIE model to develop an e-commerce system integrated with product information, automatic shipping cost calculation through the RajaOngkir API, and the Midtrans payment gateway, while also evaluating its feasibility. The results show that the e-commerce platform was successfully developed. Evaluation using the Black Box Testing method yielded a system functionality score of 84.6%, which falls within the 81%–100% range and is categorized as Highly Feasible. The findings indicate that minor input-related issues do not affect transaction stability, making the system suitable for optimizing sales among agate gemstone artisans in Tunjungmuli Village.